Model Holistik dan Kontinu: Implementasi Praktis Pendidikan Agama Kristen (PAK) Berdasarkan Ulangan 6:6-7 dalam Kehidupan Keluarga Sehari-hari - Dalle, Semuel (STT Pelita Dunia, 2025)
This study aims to analyze and develop an operational model for the implementation of Christian Religious Education (CRE) based on the Biblical mandate in Deuteronomy 6:6-7 for the nurturing of children within Christian families. The Christian family plays a vital and primary role in the faith education of children, a concept deeply rooted in the Deuteronomy 6:6-7 text. This verse emphasizes the parents' obligation to instill God's word repeatedly and consistently (continuously) and holistically, integrating it into all aspects of daily life—namely